K redefinici vybraných pojmů ve španělské translatologii optikou prací Jiřího Levého - Jana Králová (Acta Universitatis Carolinae: Philologica, 2018)
This paper aims to present a comparison between some concepts authored by contemporary Spanish translation scholars and the ideas formulated by Jiři Levy. A short outline of the evolution of Translation Studies in Spanish speaking countries in the second half of the 20th century is taken as a basis for the explanation of the lack of awareness of Levy’s theories among the Spanish speaking authors. Compared to some recent concepts studied in Spanish (the so-called anisomorfisms in translation, the problem of the source of the translating activity), the concepts attributed to Jiři Levy (translation as a decision process, the source) seem to be more dynamic and complex. Therefore, Levy’s theories can be considered as methodologically innovative, despite having been defined more than fifty years ago.